TRANSFORMATION OF MODERN AGRICULTURE INTO ORGANIC AGRICULTURE AT SUBAK WANGAYA BETAN, PENEBEL DISTRICT, TABANAN REGENCY, BALI PROVINCE - Dewi Yuliana, Euis; Ardika, I Wayan; Semadi Astra, I Gde; Antara, I Made (E-Journal of Cultural Studies, 2012)
This dissertation discusses the transformation of modern agriculture into organicagriculture at Subak Wangaya Betan, Penebel District, Tabanan Regency, Bali Province.This study is conducted in the perspective of Cultural Studies and the problem is that thedark side of modern agriculture is getting visible. The chemical substances used inagriculture have turned out to result in many problems such as the damage of landquality, the continuous decrease in plant productivity and environment, themarginalization of farmers. Therefore, many farmers have been aware and havetransformed into ecologically organic agriculture as what has taken place at SubakWangaya Betan. The farmers have transformed from modern agriculture into organicagriculture. However, the process of the transformation has left many problems;therefore, a deep study is necessarily conducted to answer various existing questions.The problems in this study are formulated in three basic questions such asfollows. First, how has the process of the transformation from modern agriculture intoorganic agriculture taken place at Subak Wangaya Betan? Second, why has thetransformation from modern agriculture into organic agriculture taken place? Third, whatare the implications and meanings of the transformation from modern agriculture intoorganic agriculture at Subak Wangaya Betan? In general, this study aims at identifyingand comprehending more clearly the transformation from modern agriculture into organicagriculture taking place at Betan Wangaya Subak.This research was conducted using qualitative method with multidisciplinaryapproach in accordance with the paradigm of cultural studies. In the first stage, primaryand secondary data were collected. In the second stage, theories were selected foranalyzing the data. Several critical theories such as the theory of Discourse of Power andKnowledge, the theory of Hegemony and the theory of Deconstruction, which are eclecticin nature, were decided to select for analyzing the data. In this third stage, the selecteddata were analyzed and interpreted. In the fourth stage, the results were constructed andreported. Based on the analysis conducted, three findings could be reported. First,agricultural transformation has taken place at Subak Wangaya Betan, from agrochemicalbasedmodern agriculture in which inorganic, chemical pesticide and hybrid varieties areused into organic agriculture in which no chemical substances are used. The agriculturaltransformation has not been suddenly conducted; it has been a planned process, has beenconducted through a highly systematic mechanism with many stages and has consumed alot of time and needed in-depth studies. Second, many factors have led to the agriculturaltransformation taking place at Subak Wangaya Betan. They are external factors such aspolitical, economic, social, cultural and ecological aspects and internal factors such as thenegative side of green revolution implementation, natural resources, cooperative farmers,and adherent farmers. They are all equally strong and synergize in encouraging andaccelerating the agricultural transformation. Third, it turns out that the agriculturaltransformation taking place at Subak Wangaya Betan has several implications andmeanings. The implications are that the ideology adhered to by the farmers has changed,the establishment of new institutions, an increase in the farmers’ income, improved ricefield ecosystem and environment. The meanings of organic agriculture are spiritualmeaning, empowerment meaning and welfare meaning.
Keywords: agricultural transformation, modern agriculture, organic agriculture, Subak Wangaya Betan.